Zakat As Tax Reduction: Study Of Muslim Community Perception In Indonesia And Malaysia - Aula Ahmad Hafidh Saiful Fikr; Fuadah Johari; Maimun Sholeh; Eko Suprayitno; Ngadiyono (Universitas Airlangga, Indonesia, 2024)
Vol. 7 No. 2 (Page 327–349)